Mass Transfer Study of Ammonia-water Falling-film Absorption in Vertical Tube - Xu Zhenzhong; Xia Zaizhong; Lin Peng; Guo Peimin; Wang Ruzhu (Zhileng xuebao)
Absorber is the key component of Ammonia-water absorption refrigeration. This study simulate the falling film adiabatic absorption to analyse the characteristics of mass absorption and compare the simulated result with the experiment result. The error of the simulated value of mass transfer rate comparing to the experiment value is less than 20%.Besides the experiment shows that subcooling of weak solution before absorption can promote the mass absorption. In experiment, cooled absorption with subcooling improve the mass absorptive rate by 132%.